Identifikasi Pola Asuh Orang Tua terhadap Perkembangan Membaca Permulaan Anak - Sari, Purnama; Sawitri, Dewi; Trisna Mukti, Suci; Siregar, Masyunita; Hasni, Uswatul; Surya Amanda, Rizki (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This research highlights the importance of reading as a key element in understanding scientific concepts, introduces written language symbols, and emphasizes the role of the family environment and children's play on reading development. Focus on children's early reading delays in grade 1 elementary school students in the JL area. HM. Kamil, Lorong Anggrek which aims to identify parenting patterns as a significant factor. Researchers try to overcome this problem by introducing activities to the concept of early reading, highlighting the importance of appropriate parenting patterns and creating an interesting learning atmosphere. Qualitative descriptive research methods were used to explore information regarding the influence of parental parenting on children's early reading development. The research results show the application of a primitive parenting style, which allows children to explore without certain stimuli. The implication of these findings is the need for a creative and varied approach to early reading learning, taking into account children's readiness and supporting the positive role of parents in forming children's interest in reading.